2013
DOI: 10.1055/s-0033-1359727
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on Uterine Embolization for Fibroids

Abstract: Strong evidence for both safety and effectiveness of uterine fibroid embolization has been generated since the procedure's introduction. This review will focus on the key articles representing the best evidence to summarize the outcomes from uterine embolization. This review will attempt to answer three important questions associated with uterine embolization. First, does uterine embolization relieve symptoms caused by uterine fibroids? Second, how well does the improvement in symptoms and quality of life afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
0
18
0
2
Order By: Relevance
“…Our patient’s symptoms have continuously improved, and she will continue to follow with both interventional radiology and gynaecology to monitor for symptom recurrence. Randomised trials and retrospective data in the literature have reported fibroid symptoms recurrence rates after UAE of 7%–35% over approximately 5 years 1 4. Patients with recurrence have been treated with both repeat embolisation and hysterectomy with good results.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient’s symptoms have continuously improved, and she will continue to follow with both interventional radiology and gynaecology to monitor for symptom recurrence. Randomised trials and retrospective data in the literature have reported fibroid symptoms recurrence rates after UAE of 7%–35% over approximately 5 years 1 4. Patients with recurrence have been treated with both repeat embolisation and hysterectomy with good results.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…Uterine artery embolisation (UAE) has been well established as a safe and effective treatment modality for both bleeding and bulk symptoms caused by uterine fibroids, with numerous randomised trials in the literature which have been summarised in subsequent review articles 1 2. Bleeding symptoms include menorrhagia, polymenorrhagia (frequent but regular uterine bleeding) and menometrorrhagia (irregular uterine bleeding); typical bulk symptoms are generalised pelvic pain or pressure, bloating, urinary frequency, constipation, incontinence and dyspareunia.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of UAE on heavy menstrual bleeding (HMB), it has been shown that most patients (73-90 %) reported improvement or disappearance of symptoms up to 5 years after treatment [ 43 ].…”
Section: Outcome Of Uaementioning
confidence: 99%
“…Since its introduction, strong evidence for safety and efficacy of UAE has been generated with low rates of complications. 5 This review will discuss UAE for the management of symptomatic uterine fibroids with special focus on emerging technical approaches and novel periprocedural patient care.…”
mentioning
confidence: 99%